ANALYSIS OF POVERTY ALLEVIATION AND FINANCIAL INCLUSION IN THE MUSTAHIK EMPOWERMENT PROGRAM IN PEKANBARU - Trianto, Budi; Nasution, Yasir; Siregar, Saparuddin (Jurnal Ekonomi & Studi Pembangunan, 2018)
This study aims to analyze poverty alleviation and financial inclusion in the mustahik empowerment program in Pekanbaru. The samples involved in this study were 105 people drawn from four organizations of zakat in Pekanbaru. The analytical technique conducted using qualitative descriptive analysis. The results of this study show that the economic empowerment program conducted by zakat institutions in Pekanbaru has succeeded in alleviating the mustahik of the poverty line. Based on the World Bank's poverty line, there are 34.07% of successful out of poverty line. Meanwhile, if using the Government poverty line then there are 60.29% mustahik who managed to get out of the poverty line. However, this empowerment program has not been integrated with the sharia microfinance institutions. Therefore, the empowerment program for mustahik should be integrated with Islamic microfinance to pursue successful financial inclusion for mustahik.